Correction of B0-induced geometric distortion variations in prospective motion correction for 7T MRI - Uten Yarach (2018)
© 2016, ESMRMB. Objective: Prospective motion correction can effectively fix the imaging volume of interest. For large motion, this can lead to relative motion of coil sensitivities, distortions associated with imaging gradients and B0field variations. This work accounts for the B0field change due to subject movement, and proposes a method for correcting tissue magnetic susceptibility-related distortion in prospective motion correction. Materials and methods: The B0field shifts at the different head orientations were characterized. A volunteer performed large motion with prospective motion correction enabled. The acquired data were divided into multiple groups according to the object positions. The correction of B0-related distortion was applied to each group of data individually via augmented sensitivity encoding with additionally integrated gradient nonlinearity correction. Results: The relative motion of the gradients, B0field and coil sensitivities in prospective motion correction results in residual spatial distortion, blurring, and coil artifacts. These errors can be mitigated by the proposed method. Moreover, iterative conjugate gradient optimization with regularization provided superior results with smaller RMSE in comparison to standard conjugate gradient. Conclusion: The combined correction of B0-related distortion and gradient nonlinearity leads to a reduction of residual motion artifacts in prospective motion correction data.